Low proliferation and differentiation capacities of adult hippocampal stem cells correlate with memory dysfunction in humans - Coras, Roland; Siebzehnrübl, Florian; Pauli, Elisabeth; Huttner, Hagen; Njunting, Marleisje; Kobow, Katja; Villmann, Carmen; Hahnen, Eric; Neuhuber, Winfried; Weigel, Daniel; Buchfelder, Michael; Stefan, Herrmann; et al. (Brain, 2010)
The hippocampal dentate gyrus maintains its capacity to generate new neurons throughout life. In animal models, hippocampal neurogenesis is increased by cognitive tasks, and experimental ablation of neurogenesis disrupts specific modalities of learning and memory. In humans, the impact of neurogenesis on cognition remains unclear. Here, we assessed the neurogenic potential in the human hippocampal dentate gyrus by isolating adult human neural stem cells from 23 surgical en bloc hippocampus resections. After proliferation of the progenitor cell pool in vitro we identified two distinct patterns. Adult human neural stem cells with a high proliferation capacity were obtained in 11 patients. Most of the cells in the high proliferation capacity cultures were capable of neuronal differentiation (53 +/- 13% of in vitro cell population). A low proliferation capacity was observed in 12 specimens, and only few cells differentiated into neurons (4 +/- 2%). This was reflected by reduced numbers of proliferating cells in vivo as well as granule cells immunoreactive for doublecortin, brain-derived neurotrophic factor and cyclin-dependent kinase 5 in the low proliferation capacity group. High and low proliferation capacity groups differed dramatically in declarative memory tasks. Patients with high proliferation capacity stem cells had a normal memory performance prior to epilepsy surgery, while patients with low proliferation capacity stem cells showed severe learning and memory impairment. Histopathological examination revealed a highly significant correlation between granule cell loss in the dentate gyrus and the same patient's regenerative capacity in vitro (r = 0.813; P < 0.001; linear regression: R-adjusted(2) = 0.635), as well as the same patient's ability to store and recall new memories (r = 0.966; P = 0.001; linear regression: R-adjusted(2) = 0.9). Our results suggest that encoding new memories is related to the regenerative capacity of the hippocampus in the human brain.
Keywords: stem cells; neurogenesis; hippocampus; memory; learning; epilepsy; doublecortin